Pengembangan Video Edukasi Kartun Animasi Bermuatan Literasi Teks Multimodal untuk Penguatan Karakter Siswa - Andry Fitrian; Yulian Dinihari; Marisha Ayuardini; Yulistiana Yulistiana; Endah Diah Parwati (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
The lack of innovation among teachers in developing instructional media can lead to problems inclassroom learning activities. Therefore, this study aims to develop an educational animated cartoon videoon the topic of Newton’s Second Law to facilitate learning for tenth-grade senior high school students. Thefocus of this research is to develop the animated educational video and to determine its effectiveness as alearning medium. This study employs a Research and Development (R&D) method by adopting the ADDIEdevelopment model (Analyze, Design, Development, Implementation, and Evaluation). Data were collectedusing a Likert-scale questionnaire, and the data analysis was conducted through validation by media experts,subject-matter experts, and language experts. The results show that the developed learning media in the formof an animated cartoon video, created using the Kinemaster application on the topic of Newton’s SecondLaw, obtained an average validation score of 75, which falls into the “good” category. Furthermore, theaverage score for the effectiveness of the animated video in student learning reached 100, which iscategorized as “very effective”.Keywords: Educational Videos, Animated Cartoons, Newton’s Second Law.